Judicial Checks and Balances - La Porta, Rafael; López‐de‐Silanes, Florencio; Pop‐Eleches, Cristian; Shleifer, Andrei (Journal of Political Economy, 2004)
In the Anglo-American constitutional tradition, judicial checks and balances are often seen as crucial guarantees of freedom. Hayek distinguishes two ways in which the judiciary provides such checks and balances: judicial independence and constitutional review. We create a new database of constitutional rules in 71 countries that reflect these provisions. We find strong support for the proposition that both judicial independence and constitutional review are associated with greater freedom. Consistent with theory, judicial independence accounts for some of the positive effect of common-law legal origin on measures of economic freedom. The results point to significant benefits of the Anglo-American system of government for freedom. This paper is a radical revision of an earlier paper by the same authors, “The Guarantees